Measuring senior english instructors' acceptance of WeCWI-Enabled Web-Based Instruction through the TAM model / Wang Jing, Dr. Boon Yih Mah and Prof. Madya Dr. Rofiza Aboo Bakar - Wang, Jing; Boon, Yih Mah; Aboo Bakar, Rofiza (Universiti Teknologi MARA, Kedah, 2025)
Despite advancements in information and communication technology (ICT) and the adoption of web-based instruction (WBI) in Chinese universities, students' writing skills are hindered by traditional teaching methods. The conventional cramming approach focuses on memorisation and exam performance rather than genuine comprehension and creativity. Instructors often revert to these outdated methods due to limited ICT skills and knowledge. WeCWI-enabled WBI, designed based on Web-based Cognitive Writing Instruction (WeCWI), was implemented in an EFL blended learning classroom at a university in China to address this problem. A hybrid instructional platform, integrating Mosoteach and WeChat Public Account, was developed to enhance English as a Foreign Language (EFL) learners' writing performance. This platform emphasises improving writing skills through substantial reading inputs, collaborative writing, and instant feedback. This paper examines senior English instructors' acceptance of WeCWI-enabled WBI to refine the approach before its full implementation in classrooms. In-depth interviews grounded in the Technology Acceptance Model (TAM) were conducted, and the data were analysed using holistic content analysis. The study aims to measure the acceptance of WeCWI-enabled WBI and help instructors design effective activities for collaborative learning. The results demonstrate the feasibility of WeCWI-enabled WBI, highlighting its clear manual and its effectiveness in stimulating students' interest. The practical implications of this research indicate that instructors significantly favour WeCWI-enabled WBI, supported by a detailed manual. They recognise that WeCWI-enabled WBI improves students' writing skills and increases their motivation and participation in learning. The study findings can help educators integrate web-based tools for better learning outcomes.